2018
DOI: 10.1007/s00270-018-1929-9
|View full text |Cite
|
Sign up to set email alerts
|

Serial Uterine Artery Embolization for the Treatment of Placenta Percreta in the First Trimester: A Case Report

Abstract: Level IV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…20 Additionally, the poor hemostatic effect induced by increased parity may be related to thinning of uterine myometrium and an increase in arteries supplying blood to the uterus. 21 Wang et al 22 showed that a mass >5 cm was a risk factor for patients with CSP who have curettage or for those with UAE combined with curettage. Our study also showed similar results.…”
Section: Discussionmentioning
confidence: 99%
“…20 Additionally, the poor hemostatic effect induced by increased parity may be related to thinning of uterine myometrium and an increase in arteries supplying blood to the uterus. 21 Wang et al 22 showed that a mass >5 cm was a risk factor for patients with CSP who have curettage or for those with UAE combined with curettage. Our study also showed similar results.…”
Section: Discussionmentioning
confidence: 99%
“…In acute causes of massive bleeding the management is similar to that of PPH (Kaufman and Tadros 2018 ; DeMeritt et al 2018 ; Shahin and Pang 2018 ; Fitzpatrick et al 2014 ; Sentilhes et al 2013 ).…”
Section: Treatmentmentioning
confidence: 99%